Homeschooling Model as An Alternative for Islamic Education - Syarifah Syarifah; Madani Ahmadan; Muhammad Thola'at Wafa (Jurnal Penelitian Pendidikan, 2024)
In the following study explores how homeschooling can be an alternative Islamic education option for Muslim families. The research method used in this research is a qualitative method with a literature review. The results obtained from the research show that (1) Homeschooling is not a current topic in Islamic education. Rasulullah pioneered homeschooling . Rasulullah educated his friends and produced outstanding students at Arqam's house. There are three types of homeschooling in the Islamic tradition: single (family) homeschooling , multiple homeschooling (halaqah), and community (mosque) homeschooling . Natural education includes monotheism, religion, morals, leadership and vocational education. (4) Family education should touch on seven aspects: faith, morals, physical, intellectual, psychological, social and sexual. (5) To instill these values, various methods need to be used, including example, advice, customs, attention, appreciation and punishment.